2011
DOI: 10.1039/c1lc20373h
|View full text |Cite
|
Sign up to set email alerts
|

‘Fab-Chips’: a versatile, fabric-based platform for low-cost, rapid and multiplexed diagnostics

Abstract: Low cost and scalable manufacture of lab-on-chip devices for applications such as point-of-care testing is an urgent need. Weaving is presented as a unified, scalable and low-cost platform for the manufacture of fabric chips that can be used to perform such testing. Silk yarns with different properties are first selected, treated with the appropriate reagent solutions, dried and handloom-woven in one step into an integrated fabric chip. This platform has the unique advantage of scaling up production using exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
128
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(134 citation statements)
references
References 15 publications
0
128
0
1
Order By: Relevance
“…Moreover, the system must be low cost, while still being robust, miniature, flexible, washable, reusable, or disposable (5). All these requirements point to microfluidic devices as the key for improving wearable chemo-and biosensing (338). Chemical measurements on bodily fluids such as blood, sweat, and urine are needed.…”
Section: Future Trends In Biomedical Sensingmentioning
confidence: 99%
“…Moreover, the system must be low cost, while still being robust, miniature, flexible, washable, reusable, or disposable (5). All these requirements point to microfluidic devices as the key for improving wearable chemo-and biosensing (338). Chemical measurements on bodily fluids such as blood, sweat, and urine are needed.…”
Section: Future Trends In Biomedical Sensingmentioning
confidence: 99%
“…These authors demonstrated that the procedure had made the silk more hydrophilic and enabled it to wick a predefined volume of coloured dye solution. 7 Nilghaz et al have used sewn cotton cloth which is inherently wettable and hydrophilic due to the porous structure of cloth formed by the gaps between the woven threads. They demonstrated that this porous structure is sufficient for providing capillary force and rapid wetting and wicking.…”
Section: -5mentioning
confidence: 99%
“…The wicking rates of low ($3 TPI), medium ($20 TPI), and high ($50 TPI) yarns were examined and it was observed that the wicking rate was increased by increasing the twist/inch. 7 Das et al modeled liquid wicking of polyester yarns and textile against gravity using the Laplace and the Hagen-Poiseuille equations, and considering the effect of gravity. In their study, pore geometry, liquid contact angle with fibre, number of fibres in a yarn, fibre denier, fibre cross-sectional shape, yarn denier, and twist level in the yarn were considered.…”
Section: Analysis Of Wicking Property In Thread and Textilementioning
confidence: 99%
See 2 more Smart Citations